Can AI Identify Novel Drug Candidates? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2020)
The traditional path of drug discovery is a notoriously long, expensive, and often-unsuccessful journey. Bringing a single new drug to market can take over a...
Keywords: Drug Discovery and Pharmaceutical AI; Identify; Novel; Candidates; Artificial Intelligence; Machine Learning